2021
DOI: 10.1101/2021.01.04.425350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular and Viral Determinants of HSV-1 Entry and Intracellular Transport towards Nucleus of Infected Cells

Abstract: HSV-1 employs cellular motor proteins and modulates kinase pathways to facilitate intracellular virion capsid transport. Previously, we and others have shown that the Akt inhibitor miltefosine inhibited virus entry. Herein, we show that the protein kinase C inhibitors staurosporine (STS) and gouml inhibited HSV-1 entry into Vero cells, and that miltefosine prevents HSV-1 capsid transport toward the nucleus. We have reported that the HSV-1 UL37 tegument protein interacts with the dynein motor complex during vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Dynein must be phosphorylated to obtain an active conformation ( 54 , 55 , 59 61 ). Recently, it was shown that upon infection of epithelial cells with HSV-1, dynein intermediate chain 1B was phosphorylated at position S80 in an Akt- and protein kinase C (PKC)-independent manner ( 62 ). It was speculated that US3’s kinase function could mediate the activation of dynein throughout the retrograde transport process.…”
Section: Discussionmentioning
confidence: 99%
“…Dynein must be phosphorylated to obtain an active conformation ( 54 , 55 , 59 61 ). Recently, it was shown that upon infection of epithelial cells with HSV-1, dynein intermediate chain 1B was phosphorylated at position S80 in an Akt- and protein kinase C (PKC)-independent manner ( 62 ). It was speculated that US3’s kinase function could mediate the activation of dynein throughout the retrograde transport process.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that upon infection of epithelial cells with HSV-1, dynein intermediate chain 1B was phosphorylated at position S80 in an Akt and PKC independent manner 58 . We have also observed dynein phosphorylation (at position T88) during PRV infection that was US3 dependent (A. D. Esteves and L. W. Enquist, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Major capsid protein ICP5 is involved in the transport of virion capsids to the nuclei. 35 During the late stage of infection, ICP5 localizes in DNA replication compartments, sites of infected cell nuclei, in which newly replicated viral DNAs insert into preformed capsids. 35,36 In the current study, fluorescence microscopy was utilized to observe HSV-1-ICP5 antibody staining positive cells; it seems that RAF265 possibly facilitates the viral entry process (Figure 2D).…”
Section: Raf265 Exhibited Inhibitory Activity At the Early Stage Of H...mentioning
confidence: 99%